ALA‐PDT regulates macrophage M1 polarization via ERK/MAPK‐NLRP3 pathway to promote the early inflammatory response. Issue 10 (20th November 2022) - Wang, Liqun; Zhang, Wentao; Cen, Ruiyan; Yue, Chenda; Xiao, Tianzhen; Deng, Yumeng; Li, Lingfei; Sun, Kedai; Lei, Xia
Abstract: Background: Photodynamic therapy (PDT) is a promising new approach to promote wound healing and its effectiveness has been demonstrated in both clinical and animal studies. Macrophages are the key cells in wound healing and inflammatory response. However, the mechanism of action of PDT on macrophages in promoting wound healing is still unclear. Methods: In this study, RAW264.7 cells were used. We analyzed the expression levels of macrophage markers arginase 1 (Arg‐1), CD206, iNOS, CD86, and inflammatory factors IL‐6, TNF‐α, and IL‐1β by reverse transcription‐polymerase chain reaction and Western blot, Milliplex microtubule‐associated protein multiplex assay was performed to analyze the expression of inflammatory factors in the supernatant. Live cell Imaging System to observe the dynamic process of macrophage phagocytosis. Western blot was performed to observe the activation of extracellular signal‐regulated kinase/mitogen‐activated protein kinase (ERK/MAPK) and NOD‐like receptor protein 3 (NLRP3) inflammasome. Results: 5‐Aminolevulinic acid (ALA)‐PDT increased the expression of M1 marker iNOS/CD86 and decreased the expression of Arg‐1/CD206 in RAW264.7 cells, while, proinflammatory factors IL‐6, TNF‐α, and IL‐1β expression was enhanced and macrophage phagocytosis was increased. We also found that these phenomena were associated with activation of the ERK/MAPK‐NLRP3 pathway. Conclusion: ALA‐PDT promotes early inflammatory responses by regulating macrophage M1 polarization through the ERK/MAPK‐NLRP3 pathway. It also promotes macrophage phagocytosis.